On the Forecasting Properties of the Alternative Leading Indicators for the German GDP: Recent Evidence - Konstantin Arkadievich Kholodilin; Boriss Siliverstovs (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
In this paper we perform a comparative study of the forecasting properties of the alternative leading indicators for Germany using the growth rates of German real GDP. We use the post-unification data which cover years from 1991 through 2004. We detect a structural break in the growth rates that occurs in the first half of 2001. Our results suggest that the forecasting ability of the leading indicators has been rather good in the pre-break period but it significantly deteriorated in the post-break period, i.e. in 2001?2004. None of the leading indicator models was able to predict and accommodate the structural break in the growth rates of the time series under scrutiny.
Keywords: C10; E32; 330; Forecasting real GDP; diffusion index; leading indicators; PcGets